Venous thromboembolism in cancer patients – Risk scores and recent randomised controlled trials - Thaler, Johannes; Ay, Cihan; Pabinger, Ingrid (Thrombosis and Haemostasis, 2012)
Cancer patients are at increased risk of developing venous thromboembolism (VTE). Guidelines recommend routine thromboprophylaxis in hospitalised acutely ill cancer patients and in myeloma patients receiving combination treatments including thalidomide or lenalidomide. Currently, thromboprophylaxis is not recommended in cancer out-patients. It is the aim of this review to give an overview of studies that applied scores for the risk assessment of cancer-related VTE. We will also discuss randomised controlled trials (RCTs) that investigated primary thromboprophylaxis in cancer patients. Recently, Khorana et al. published a practical and reproducible risk assessment score that includes clinical and laboratory parameters for the stratification of cancer patients according to their propensity to develop VTE. Patients assigned to the high-risk group are likely to benefit most from primary thromboprophylaxis. This score was validated in prospective and retrospective observational studies. In the Vienna Cancer and Thrombosis Study (CATS) the score was expanded by adding two biomarkers, and the prediction of VTE was considerably improved. In recent RCTs including cancer patients with different malignancies it was shown that thromboprophylaxis is safe and effective. However, VTE incidence rates were low. To date, no data is available from interventional studies applying thromboprophylaxis in cancer patients categorised into high-risk groups on the basis of risk assessment with scores. From the available literature we conclude that risk assessment for VTE is feasible in cancer patients;however, interventional studies to investigate the safety and efficacy of thromboprophylaxis in a high risk cancer population have yet to be performed.
Keywords: Cancer; venous thrombosis; risk assessment; randomised controlled trials